OCCURRENCE OF Bregmaceros nectabanus (WHITLEY, 1941) IN THE GULF OF ANTALYA - Ferhat Çağıltay; Mehmet Gökoğlu; B. Ahmet Balcı; Alper Yıldız (AQUASAINS, 2023)
With the opening of the Suez Canal in 1869, a connection was established between the Red Sea and the Mediterranean. Because of this connection, many organisms of Red Sea origin migrated to the Mediterranean. These migratory organisms also include fish. For this reason, we monitor and determine the number of fish originating from the Red Sea in the Gulf of Antalya. One of the fishing methods in the Gulf of Antalya is trawler fishing. One of the fish species caught during commercial trawling is horse mackerel. A small and different type of fish was found in the stomach of horse mackerel caught during trawling on October 26, 2021 in the Gulf of Antalya. During the species identification of these fish samples, which were intact in the stomach content of horse mackerel and preserved their integrity, it was determined that these fish were Bregmaceros nectabanus, which is included in the Bregmacerotidae family. With this study, the presence of B. nectabanus identified in the Gulf of Antalya was one more addition to the number of Red Sea origin fish species in the Gulf.